Shear bond strength of calcium silicate-based cements to glass ionomers - Ruken Ergül; Seçkin Aksu; Seçil Çalışkan; Nuray Tüloğlu (BMC, 2024)
Abstract Background A shear bond strength between the biomaterial and restorative material is crucial for minimizing bacterial microleakage and ensuring a favorable long-term prognosis for vital pulp therapy. This study aimed to conduct a comparative evaluation of the shear bond strength between calcium silicate-based biomaterials utilized in vital pulp treatment and various glass ionomer cement materials, both with and without the application of adhesive agents. Methods A total of 270 acrylic blocks, each featuring cavities measuring 4 mm in diameter and 2 mm in depth, were prepared. Calcium silicate-containing biomaterials (ProRoot MTA, Medcem Pure Portland Cement, and Medcem MTA), following manufacturers' instructions, were placed within the voids in the acrylic blocks and allowed to set for the recommended durations. The biomaterial samples were randomly categorized into three groups based on the restorative material to be applied: conventional glass ionomer cement, resin-modified glass ionomer cement, and bioactive restorative material. Using cylindrical molds with a diameter of 3.2 mm and a height of 3 mm, restorative materials were applied to the biomaterials in two different methods, contingent on whether adhesive was administered. After all samples were incubated in an oven at 37 °C for 24 h, shear bond strength values were measured utilizing a universal testing device. The obtained data were statistically evaluated using ANOVA and post-hoc Tukey tests. Results The highest shear bond strength value was noted in the Medcem MTA + ACTIVA bioactive restorative material group with adhesive application, while the lowest shear bond strength value was observed in the ProRoot MTA White + Equia Forte HT Fil group without adhesive application (P < 0.05). Conclusion Activa Bioactive Restorative may be considered a suitable restorative material in combination with calcium silicate-based biomaterials for vital pulp treatment. The application of adhesives to calcium silicate-based biomaterials can effectively address the technical limitations.